BPAP is an effective second‐line therapy for obese patients with OSA failing regular CPAP: A prospective observational cohort study. Issue 4 (12th August 2019) - Ishak, Athanasius; Ramsay, Michelle; Hart, Nicholas; Steier, Joerg
ABSTRACT: Background and objective: Continuous positive airway pressure (CPAP) is the most common treatment for obstructive sleep apnoea (OSA), but many patients fail long‐term therapy. Bilevel positive airway pressure (BPAP) is a potential alternative. We hypothesized that BPAP could improve treatment adherence and outcomes in patients who cannot tolerate CPAP. Methods: Patients with OSA who failed CPAP (usage < 4 h/day) and were referred to a tertiary sleep centre between 2014 and 2017 for BPAP were included. Age, gender, body mass index (BMI), co‐morbidities, CPAP use and reasons for failure, Epworth Sleepiness Scale (ESS), sleep study data, spirometry data and average maximum nightly compliance were recorded. Results: A total of 52 patients with OSA requiring CPAP > 15 cm H2 O (71% male, age: 58 (15) years, BMI: 42.6 (10.1) kg/m 2, apnoea–hypopnoea index (AHI): 51.1 (30.4)/h) were studied; 62% had respiratory co‐morbidities affecting nocturnal breathing including obesity hypoventilation syndrome and COPD; 25% had neuromuscular conditions; and 17% had cardiovascular disease. CPAP was used for 199 (106–477) days prior to referral for BPAP. Reasons for CPAP failure were intolerant pressures (23%), uncontrolled symptoms (23%), mask problems (21%), adverse effects (13%), claustrophobia (8%), co‐morbidities (8%) and other issues (4%). Lower expiratory positive airway pressures were needed with BPAP compared to CPAP (10 (8–12) vs 16.8 (15.7–19.2) cm H2 O, P = 0.001); patients achieved better adherence to BPAP (7.0 (4.0–8.5) vs 2.5 (1.6–6.7) h/night, P = 0.028) and better symptom control (ESS: 4.0 (1.0–7.0) vs 10.0 (6.0–17.0) points, P = 0.039). Conclusion: In patients with moderate–severe OSA who fail CPAP therapy due to low adherence, BPAP is well tolerated and achieves sufficient control of sleep‐disordered breathing and its symptoms. Abstract : There is a lack of effective alternative treatments for patients with obstructive sleep apnoea (OSA) who do not tolerate continuous positive airway pressure (CPAP) therapy. We investigated whether bilevel positive airway pressure (BPAP) could be an effective second‐line therapy in this cohort of patients and found that BPAP significantly improved adherence and symptom control when compared to CPAP. See related Editorial